Pengaruh Kualitas Pelayanan dan Budaya Organisasi terhadap Ketepatan Investigasi Incident Management di Pusintek Kementerian Keuangan RI - Trisna Febriana (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The purpose of this research is to verify and estimate the correlation of Quality Service, that consist of Tangible, Reliability, Responsiveness, Assurance, Empathy, and Organizational Culture, that consist of Power Distance Index (PDI), Individualism Index, Masculinity Index, Uncertainty Avoidance Index (UAI) againstIncident Management’s Accuracy of Inconvenience Investigation, to identify dominant indicator of Quality Service variable and to identify dominant indicator of Organizational Culture Variable. This research use a quantitative descriptive approaching with the questioner as a primary data and literature comparation as asecondary data, and is a non-experimentally research. The model is developed, in this research is consist of two hypotheses that are examined by The Structural Equation Model (SEM) method using Lisrel 8.80 as an analysis tool. The sample that is used in this research is to the tune of 287 respondents from the Ministry of Finance with random sampling technique. The result of this research, based on fit model, obtain that all of the tvalue indicator of exogen variable are greater than ttable (N=287; α=0.05) as much as 1.97. In conclusion, this research isclearly state that H0 is reected and H1 is accepted, which means there is a significant correlation between Quality Service and Organizational Culture against Investigation Accuracy simultaneously. (TF).